Effective inhibition of Salmonella Typhimurium in fresh produce by a phage cocktail targeting multiple host receptors. (February 2019) - Bai, Jaewoo; Jeon, Byeonghwa; Ryu, Sangryeol
Abstract: Salmonella contamination of fresh produce is the primary bacterial cause of a significant number of foodborne outbreaks and infections. Bacteriophages can be used as natural antibacterial agents to control foodborne pathogens. However, the rapid development of bacterial resistance to phage infection is a significant barrier to practical phage application. To overcome this problem, we developed a novel phage cocktail consisting of the three phages (BSPM4, BSP101 and BSP22A) that target different host receptors, including flagella, O-antigen and BtuB, respectively. Whole genome sequence analysis of the phages revealed that three phages do not harbor genes involved in lysogen formation or toxin production, suggesting they are safe for use as biocontrol agents in foods. In vitro treatment of the phage cocktail resulted in a significant reduction in the development of bacterial resistance. Phage cocktail treatments achieved 4.7–5.5 log CFU/cm 2 reduction of viable cell number in iceberg lettuce and 4.8–5.8 log CFU/cm 2 reduction in cucumber after 12 h at room temperature (25 °C). The phage cocktail exhibited good antimicrobial efficiency, suggesting that it could reduce S . Typhimurium contamination of fresh produce. The strategy of developing cocktails of phages that target multiple host receptors can be used to develop novel biocontrol agents of S . Typhimurium. Highlights: Receptors of Salmonella Typhimurium-targeting bacteriophages were identified. A three-phage cocktail targeting different receptors was developed. Simultaneous targeting of three different receptors reduced the development of resistance. Phage cocktails represent promising biocontrol agents.